البرنامج النووي لكوريا الشمالية تواجهه الوكالة الدولية للطاقة الذرية - بن صويلح أ.آمال بنت احمد (مجلة العلوم السياسية, 2019)
لخلاصة Nuclear energy is among the most important discoveries reached by the human terms contributed to the solution of many problems faced by the states. The last of these that are not only utilizing it in a peaceful area, but tended toward the military field and the nuclear weapons industry , Among these countries, we find North Korea, which has openly declared their manufacture of nuclear weapons and thus entry to the club of nuclear countries. International Atomic Energy Agency has worked to resolve the North Korea standoff but has not been able to achieve positive results, prompting the intervention of European countries in order to end the crisis. تعدُّ الطاقة النووية من بين أهم الاستكشافات التي توصل إليها الإنسان إذ ساهمت في حلِّ العديد من المشاكل التي واجهت الدول . هذه الأخيرة التي لم تكتفي بتوظيفها في المجال السلمي بل اتجهت نحو المجال العسكري وصناعة السلاح النووي .من بين هذه الدول نجد كوريا الشمالية التي أعلنت صراحة صناعتها للسلاح النووي ودخولها بذلك لنادي الدول النووية . عملت الوكالة الدولية للطاقة الذرية على حلِّ أزمة كوريا الشمالية لكنها لم تتمكن من تحقيق نتائج ايجابية ما دفع لتدخل دول أوروبية قصد إنهاء الأزمة. الكلمات المفتاحية : البرنامج النووي ،كوريا الشمالية ، التسلح النووي